Helping the medicine go down: the role of the healthcare professional in a young person’s experience of achalasia, a rare oesophageal motility disorder - Geena Capps (Orphanet Journal of Rare Diseases)
Abstract Young patients can be uniquely vulnerable to the impacts of a rare disease, diagnosed in their critical years of identity formation, social development, and planning for the future. Drawing from my journey as both a rare disease patient and a medical student, this essay explores how the rare disease achalasia has shaped my life, alongside the experiences of another young patient, Isobel. Most importantly, this essay highlights the critical role that individual healthcare professionals play in shaping young patients’ experiences of their condition. Although diagnosing and managing rare diseases can be challenging due to limited research and awareness, my own experiences demonstrate that individual, intentional changes can have profound impacts. By engaging with and believing young patients, individual healthcare providers can reduce misdiagnoses, alleviate isolation and uncertainty, and ultimately, improve healthcare outcomes for young people with rare diseases.